(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
A petition had been filed before Chhattisgarh High Court seeking termination of pregnancy under the provisions of Medical Termination of Pregnancy Act, 1971. It was submitted that the petitioner was subjected to rape for which an FIR was lodged on 09.05.2021 vide Annexure P-2 and the case was registered under sections 376, 376 (2) by result of such rape she conceived. It was contended that if she was forced to continue the pregnancy which is caused by rape anguish would be caused and would eventually constitute a grave injury to the mental health of the pregnant woman. In Suchita Srivastava vs. Chandigarh Admn2009 [R] a Bench of three Judges held “a woman’s right to make reproductive choices is also a dimension of ‘personal liberty’ as understood under Article 21 of the Constitution”. The Court there dealt with the importance of the consent of the pregnant woman as an essential requirement for proceeding with the termination of pregnancy. The explanation clause of Section 3 of Act of 1971 takes within its ambit not only the physical injury but also to mental injury and anguish. It is obvious that if the victim is subjected to rape and if she is forced to give birth to a child in the social scenario she has to face a life time anguish apart from the fact the child who is born will also have to face disdain of the society. Under the circumstances, it is directed that the petitioner shall be entitled to medical termination of pregnancy. In order to carry out the Pregnancy, State shall form a panel of expert doctors at the District Hospital Durg as early as possible and DNA of the child shall also be preserved.